Res Romanae: Cultural Politics in Quintus Smyrnaeus' Posthomerica and Nonnus' Dionysiaca - Hadjittofi, Fotini (2016)
1 Res Romanae : Cultural Politics in Quintus Smyrnaeus’ Posthomerica and Nonnus’ Dionysiaca * Abstract This paper juxtaposes Quintus’ Posthomerica and Nonnus’ Dionysiaca in terms of the political and ideological positions they adopt towards Rome, and argues that the way they represent Hellenic and Roman identities is characteristic of the different cultural environments in which they were written. The first section is concerned with the characterisation of Aeneas and Sinon in Books 11-13 of the Posthomerica ; Quintus’ depiction of these two characters reflects a contestation and re-negotiation between Roman and Greek identities, which is typical of the Second Sophistic period. The following section contrasts the treatment of the Pleiad Electra and the myths relevant to her in the two epics, in order to elucidate the differences between Quintus’ and Nonnus’ attitudes towards the Roman Empire. Finally, the third part of the paper turns to the question of Nonnus’ embrace of Rome and Roman ideology, and briefly examines the phenomenon of the collapse of traditional Hellenism in Late Antiquity, as it is expressed in Book 41 of the poem, the story of Beirut.